Factores de riesgos y su relación en la trombosis venosa profunda en pacientes hospitalizados del IEES Babahoyo, octubre 2024 - mayo 2025 - Jaramillo Bajaña, Carla Julecsy (2025)
The main objective of this research was to identify and analyze the risk factors associated with deep vein thrombosis (DVT) in hospitalized patients at the IESS Babahoyo, during the period from October 2024 to May 2025. A descriptive and cross-sectional approach was applied, conducting surveys with 80 patients and 29 nurses to gather information about their sociodemographic characteristics, lifestyle habits, clinical and family history, as well as the prevention strategies implemented. In addition, the Caprini scale was modified to classify the risk of DVT in each patient, considering factors such as age, coexisting diseases, acute situations (trauma, infections, recent surgeries) and special conditions (long trips, use of oral contraceptives). The findings revealed that most of the patients belong to intermediate and advanced age groups, with a male predominance and a high prevalence of coexisting diseases and family history of chronic diseases. The use of the Caprini scale showed that the majority had a moderate score (3–4 points), placing these patients in a moderate risk category for the development of DVT. A greater use of pharmacological prophylaxis was also observed, complemented to a lesser extent with physical interventions and educational actions. In summary, this research highlights the relevance of carrying out a complete assessment of DVT risk using tools such as the Caprini scale and the adoption of integrated and personalized preventive measures. Ongoing education of both nursing staff and patients is essential to improve hospital care and minimize DVT- related complications.